2022
DOI: 10.3390/languages7020144
|View full text |Cite
|
Sign up to set email alerts
|

What Heritage Bilinguals Tell Us about the Language of Emotion

Abstract: Variation in the language experience of bilinguals has consequences for cognitive and affective processes. In the current study, we examined how bilingual experience influences the relationship between language and emotion in English among a group of Spanish–English heritage bilinguals on an emotion–memory task. Participants rated the emotionality of English taboo, negative and neutral words and then completed an unexpected recognition test. To account for language experience, data were gathered on the partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…In other words, the HL -Spanish in our studyemerged as a particularly emotional language when recalling AMs, even if our participants self-reported a slightly lower proficiency level in their HL Spanish compared with the societal language (German). Although this finding differs from previous studies among bilinguals that used retrieval tasks or decontextualised emotional situations (Ferré et al, 2010;Vañó & Pennebaker, 1997;Vargas Fuentes et al, 2022), it allows us to conclude that the use of AMs as a methodological technique may provide useful information by uncovering heritage speakers' emotional competences. Using this technique, our study found that emotional vocabulary is particularly salient in the HL, especially when heritage speakers have the opportunity to express and explain their emotions in relation to contextualised memories that have a personal meaning for them.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In other words, the HL -Spanish in our studyemerged as a particularly emotional language when recalling AMs, even if our participants self-reported a slightly lower proficiency level in their HL Spanish compared with the societal language (German). Although this finding differs from previous studies among bilinguals that used retrieval tasks or decontextualised emotional situations (Ferré et al, 2010;Vañó & Pennebaker, 1997;Vargas Fuentes et al, 2022), it allows us to conclude that the use of AMs as a methodological technique may provide useful information by uncovering heritage speakers' emotional competences. Using this technique, our study found that emotional vocabulary is particularly salient in the HL, especially when heritage speakers have the opportunity to express and explain their emotions in relation to contextualised memories that have a personal meaning for them.…”
Section: Discussioncontrasting
confidence: 99%
“…We further speculated that high trait EI participants would use a more diverse emotional vocabulary, regardless of the valence of their AMs (Beheshti et al, 2020;Le Hoang & Grégoire, 2021). With regard to language status and following previous studies involving early or balanced bilinguals (Ferré et al, 2010;Vañó & Pennebaker, 1997;Vargas Fuentes et al, 2022), we expected that our bilingual participants would retrieve more emotional words in their L2 German. We also hypothesised that bilinguals' emotional vocabulary would be less diverse in their HL Spanish than in their L2 German due to the reduced availability of general vocabulary in the HL (Montrul & Polinsky, 2021).…”
Section: The Current Studymentioning
confidence: 86%
“…Of equal relevance is that language dominance can shift in a bilingual’s lifetime, which is the typical case of bilingual children who learn a L1 in the home that is different from the one used in the school and spoken in the society at large (Peña et al, 2021). Considering language dominance as a multidimensional construct, as measured by the Bilingual Language Profile questionnaire (Birdsong et al, 2012), empirical studies have demonstrated that language dominance predicts HL bilinguals’ production of phonetic features that align to monolingual norms as well as their processing of emotional words in the societal language (Amengual, 2016; Vargas Fuentes et al, 2021). However, with respect to HL writing, very little is known about the role of language dominance.…”
Section: Introductionmentioning
confidence: 99%